The draft nuclear genome sequence and predicted mitochondrial proteome of Andalucia godoyi, a protist with the most gene-rich and bacteria-like mitochondrial genome - Gray, Michael W. (BMC Biol, 2020)
BACKGROUND: Comparative analyses have indicated that the mitochondrion of the last eukaryotic common ancestor likely possessed all the key core structures and functions that are widely conserved throughout the domain Eucarya. To date, such studies have largely focused on animals, fungi, and land plants (primarily multicellular eukaryotes); relatively few mitochondrial proteomes from protists (primarily unicellular eukaryotic microbes) have been examined. To gauge the full extent of mitochondrial structural and functional complexity and to identify potential evolutionary trends in mitochondrial proteomes, more comprehensive explorations of phylogenetically diverse mitochondrial proteomes are required. In this regard, a key group is the jakobids, a clade of protists belonging to the eukaryotic supergroup Discoba, distinguished by having the most gene-rich and most bacteria-like mitochondrial genomes discovered to date. RESULTS: In this study, we assembled the draft nuclear genome sequence for the jakobid Andalucia godoyi and used a comprehensive in silico approach to infer the nucleus-encoded portion of the mitochondrial proteome of this protist, identifying 864 candidate mitochondrial proteins. The A. godoyi mitochondrial proteome has a complexity that parallels that of other eukaryotes, while exhibiting an unusually large number of ancestral features that have been lost particularly in opisthokont (animal and fungal) mitochondria. Notably, we find no evidence that the A. godoyi nuclear genome has or had a gene encoding a single-subunit, T3/T7 bacteriophage-like RNA polymerase, which functions as the mitochondrial transcriptase in all eukaryotes except the jakobids. CONCLUSIONS: As genome and mitochondrial proteome data have become more widely available, a strikingly punctuate phylogenetic distribution of different mitochondrial components has been revealed, emphasizing that the pathways of mitochondrial proteome evolution are likely complex and lineage-specific. Unraveling this complexity will require comprehensive comparative analyses of mitochondrial proteomes from a phylogenetically broad range of eukaryotes, especially protists. The systematic in silico approach described here offers a valuable adjunct to direct proteomic analysis (e.g., via mass spectrometry), particularly in cases where the latter approach is constrained by sample limitation or other practical considerations.